PERAN KOMUNIKASI ISLAM DALAM PENYELESAIAN KONFLIK SOSIAL PADA MASYARAKAT MULTIKULTURAL - mulahazhah, hilwi (Hudan Lin Naas: Jurnal Ilmu Sosial dan Humaniora, 2025)
Social conflict is a frequent phenomenon in multicultural societies, where different groups with different cultural, religious, and ethnic identities coexist. Existing social conflicts are often resolved in bad ways so that they give rise to prolonged conflicts and even often cause new conflicts that are increasingly widespread. This condition is exacerbated by the movement of secularization or separation between worldly things and the religious realm, in this case Islam. Religious teachings are narrowed down to only religious issues. This research discusses how Islamic communication can play a role as a solution in resolving social conflicts in multicultural societies. Through a communication approach based on Islamic values, it is hoped that it can reduce tensions between groups and create peace. The purpose of this research is to provide an explanation of the resolution of social conflicts with the principles of Islam. The methodology used in this study is a literature review by analyzing communication theories, conflict concepts, and Islamic communication principles. This research is based on the view that the Qur'an and Hadith as the main guidelines in human life have provided principles in every aspect of life including communication. The results show that Islamic communication can be an effective means of promoting tolerance, understanding differences, and encouraging peaceful resolution of social conflicts. Therefore, this research is very important as an overview of Islamic communication which can not only be applied in religious practices but can be presented in every dimension of life, especially in multicultural societies. Islamic communication can be present as a solution to any social conflict that exists both for Muslims and non-Muslims.